IL-33/Vitamin D Crosstalk in Psoriasis-Associated Osteoporosis - De Martinis, Massimo; Ginaldi, Lia; Sirufo, Maria Maddalena; Bassino, Enrica Maria; De Pietro, Francesca; Pioggia, Giovanni; Gangemi, Sebastiano (Frontiers in Immunology, 2021)
Patients with psoriasis (Pso) and, in particular, psoriatic arthritis (PsoA) have an increased risk of developing osteoporosis (OP). It has been shown that OP is among the more common pathologies associated with Pso, mainly due to the well-known osteopenizing conditions coexisting in these patients. Pso and OP share common risk factors, such as vitamin D deficiency and chronic inflammation. Interestingly, the interleukin (IL)-33/ST2 axis, together with vitamin D, is closely related to both Pso and OP. Vitamin D and the IL-33/ST2 signaling pathways are closely involved in bone remodeling, as well as in skin barrier pathophysiology. The production of anti-osteoclastogenic cytokines, e.g., IL-4 and IL-10, is promoted by IL-33 and vitamin D, which are stimulators of both regulatory and Th2 cells. IL-33, together with other Th2 cytokines, shifts osteoclast precursor differentiation towards macrophage and dendritic cells and inhibits receptor activator of nuclear factor kappa-B ligand (RANKL)-induced osteoclastogenesis by regulating the expression of anti-osteoclastic genes. However, while the vitamin D protective functions in OP and Pso have been definitively ascertained, the overall effect of IL-33 on bone and skin homeostasis, because of its pleiotropic action. Emerging evidence suggests a functonal link between vitamin D and the IL-33/ST2 axis, which acts through hormonal influences and immune-mediated effects, as well as cellular and metabolic functions. Based on the actions of vitamin D and IL-33 in Pso and OP, here, we hypothesize the role of their crosstalk in the pathogenesis of both these pathologies.